Spontaneous pneumomediastinum in patients with COVID-19: A case series - Kayastha, Prakash; Paudel, Sharma; Regmi, Pradeep Raj; Ghimire, Prasoon; Adhikari, Govinda; Maharjan, Santosh; Upadhyaya, Rudra Prasad; Tuladhar, Sasmita (Grande Medical Journal, 2021)
As the COVID-19, pneumonia has evolved into global pandemic and with increase in numbers of various strains, wide range of imaging findings are being recognised. One of the rare imaging findings seen in patients with COVID-19 pneumonia is pneumomediastinum. Although most of the cases of pneumomediastinum are related to barotrauma secondary to iatrogenic intubation and mechanical ventilation, there have been multiple cases presenting with spontaneous pneumomediastinum. Here we describe five different COVID-19 positive patients who were diagnosed with spontaneous pneumomediastinum in CT scan of chest. Exact mechanism regarding this is still being debated nevertheless; one theory states the cause as diffuse alveolar injury due to cytokine storm and inflammatory response. The resultant air then tracks along the peribronchial and perivascular sheath to the mediastinum. Pneumomediastinum can have life threatening consequences and represent poor prognosis of the patients.